Intramuscular Cobinamide Sulfite in a Rabbit Model of Sub-Lethal Cyanide Toxicity - Brenner, Matthew (2010)
OBJECTIVE: To determine the ability of an intramuscular cobinamide sulfite injection to rapidly reverse the physiologic effects of cyanide toxicity. BACKGROUND: Exposure to cyanide in fires and industrial exposures and intentional cyanide poisoning by terrorists leading to mass casualties is an ongoing threat. Current treatments for cyanide poisoning must be administered intravenously, and no rapid treatment methods are available for mass casualty cyanide exposures. Cobinamide is a cobalamin (vitamin B(12)) analog with an extraordinarily high affinity for cyanide that is more water-soluble than cobalamin. We investigated the use of intramuscular cobinamide sulfite to reverse cyanide toxicity induced physiologic changes in a sublethal cyanide exposure animal model. METHODS: New Zealand white rabbits were given 10 mg sodium cyanide intravenously over 60 minutes. Quantitative diffuse optical spectroscopy and continuous wave near infrared spectroscopy monitoring of tissue oxy- and deoxyhemoglobin concentrations were performed concurrently with blood cyanide level measurements and cobinamide levels. Immediately after completion of the cyanide infusion, the rabbits were injected intramuscularly with cobinamide sulfite (n=6) or inactive vehicle (controls, n=5). RESULTS: Intramuscular administration led to rapid mobilization of cobinamide and was extremely effective at reversing the physiologic effects of cyanide on oxyhemoglobin and deoxyhemoglobin extraction. Recovery time to 63% of their baseline values in the central nervous system was in a mean of 1032 minutes in the control group and 9 minutes in the cobinamide group with a difference of 1023 minutes (95% confidence interval [CI] 116, 1874 minutes). In muscle tissue, recovery times were 76 and 24 minutes with a difference of 52 minutes (95% CI 7, 98min). Red blood cell cyanide levels returned towards normal significantly faster in cobinamide sulfite-treated animals than in control animals. CONCLUSIONS: Intramuscular cobinamide sulfite rapidly and effectively reverses the physiologic effects of cyanide poisoning, suggesting that a compact cyanide antidote kit can be developed for mass casualty cyanide exposures.